Corporate Expectations Regarding the Role of the Controller: Results of a Hungarian Survey - Fenyves, Veronika (International Review of Management and Marketing, 2019)
The past few years have seen fast and continuous changes in the corporate environment. Only those companies can stay competitive in today's economy that is able to give the right responses to the changes in their environment. Consequently, controlling activities are taking on an increasingly important role in the operation of corporate organizations. In Hungary, the role of controlling has been improving and continuously growing since the 1990s, and it has now become a management function. When setting up a new controlling system, the controller is responsible for selecting the tools, methods, and techniques that are necessary to achieve corporate goals. The study aims to identify the competencies that are required for a controller, as well as the areas they need to focus on in order to be successful in their job. The questionnaire was compiled with the help of the EvaSys system, and they were addressed to the top managers, financial managers, and controllers of various corporate organizations. The sample was made up of 124 completed and assessable questionnaires. In order to analyze the database, there were applied distribution coefficients, Ï‡2 test, Cramer's V test. Keywords: controller; organizational requirements; personal ability; personal competencies JEL Classifications: M12; M40 DOI: https://doi.org/10.32479/irmm.8566